The determinants of trust in supplier–automaker relationships in the US, Japan, and Korea - Dyer, Jeffrey H; Chu, Wujin (Journal of International Business Studies, 2011)
We examine the determinants of trust in 453 supplier–automaker relationships in the US, Japan, and Korea. We define trust and derive a model of its determinants drawing upon (1) an embeddedness (relationship-based) perspective, (2) a process-based perspective, and (3) an economic (hostage-based) perspective. Our findings indicate strong support for the process-based perspective in all countries; embeddedness was only important in Japan, and the economic hostage-based variable (stock ownership) was not important in any country.